Biocompatible materials for orbital wall reconstruction - an overview - Vasile, Victor A. (2022)
The reconstruction of an orbit after complex craniofacial fractures can be extremely demanding. For satisfactory functional and aesthetic results, it is necessary to restore the orbital walls and the craniofacial skeleton using various types of materials. The reconstruction materials can be divided into autografts (bone or cartilage tissue) or allografts (metals, ceramics, or plastic materials, and combinations of these materials). Over time, different types of materials have been used, considering characteristics such as their stability, biocompatibility, cost, safety, and intraoperative flexibility. Although the ideal material for orbital reconstruction could not be unanimously identified, much progress has been achieved in recent years. In this article, we summarise the advantages and disadvantages of each category of reconstruction materials. We also provide an update on improvements in material properties through various modern processing techniques. Good results in reconstructive surgery of the orbit require both material and technological innovations.